Biomass co-combustion process assessment using series of flame images - Kotyra, A.; Wójcik, W.; Gromaszek, K. (Искусственный интеллект, 2013)
The article presents the way of assessment of biomass coal mixture combustion using information in a form
of flame area changes determined for image sequences. The images were captured by a dedicated visual
system equipped with CMOS camera and a borescope that enabled observing flame zone located near burner
at 45° to flame axis. Several laboratory combustion experiments were carried out when thermal power and
excess air coefficient were set independently for fuel mixtures with biomass content of 10% and 20%. У статті представлений метод оцінювання спалювання суміші біомаси та вугілля при використанні
площ полум’я, які визначені в серіях зображень. Зображення були зареєстровані спеціальної відео-
системою, що складається з КМОП камери і бароскопа. Тому можна було спостерігати зону полум’я
безпосередньо близько пальники під кутом 45 градусів до її осі. Проведено серію експериментів, в
яких незалежно змінювалися теплова потужність установки і коефіцієнт надлишку повітря для сумішей з
вмістом 10% і 20% біомаси. В статье представлен метод оценивания сжигания смеси биомассы и угля при использовании
площадей пламени, которые определенные в сериях изображений. Изображения были зарегистрированы
специальной видео-системой, состоящей из КМОП камеры и бароскопа. Поэтому можно было наблюдать
зону пламени непосредственно около горелки под углом 45 градусов к её оси. Проведено серию
экспериментов, в которых независимо изменялись тепловая мощность установки и коэффициент избытка
воздуха для смесей с содержанием 10% и 20% биомассы.